The Development of International Law on Agricultural Biotechnology - Efendi, A’an; Susanti, Dyah Ochtorina; Sari, Nuzulia Kumala (Kertha Patrika; Vol 44 No 2 (2022)DO - 10.24843/KP.2022.v44.i02.p.01, 2022)
The agricultural biotechnology laws and regulations are sectoral and are spread out in various separate laws and regulations. This pattern has implications for overlapping content and difficulties in law enforcement. Another weakness is that agricultural biotechnology laws and rules do not comprehensively contain international legal principles that have been agreed globally to protect public health and the environment from the risks of using agricultural biotechnology. This study sets out three formulations of the problem: (1) why the renewal of legislation on agricultural biotechnology must be based on international law?; (2) what are the principles of international law as a source of renewal of legislation on agricultural biotechnology?; and (3) how is the implementation of international legal principles in agricultural biotechnology legislation? In this research using the type of normative legal research with a statute legal approach and a conceptual approach , three answers were obtained. First, international law is material for updating agricultural biotechnology legislation because of its strong influence on developing national law both now and in the future. Second, the principle of international law as a source of renewal of agricultural biotechnology legislation includes the principle of state sovereignty, the principle of prevention, the principle of prudence, the principle of polluters paying, the principle of cooperation, the principle of equal responsibility with different obligations, the principle of sustainable development, and the principle of participation public. Third, the implementation of the principles of international law is not carried out comprehensively but sporadically and is placed in the chapter on the principles, objectives, and scope of the law in question, not formulated in the form of a norm that has the legal force to be implemented.